THE INFLUENCE OF PARENTS' ATTITUDES IN PROVIDING EDUCATION AT HOME TOWARD THE DEVELOPMENT OF CHILDREN AGED 5-6 YEARS IN BULUSARI VILLAGE, GEMPOL SUB-DISTRICT, PASURUAN DISTRICT - Siti Fithrotul Umami; Titiek Idayanti (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Development is increasing ability (skill) in the structure and function of the body that is more complex in a regular pattern and can be predicted as a result, from the results of maturation. attitude is an individual evaluation in the form of a tendency (Inclination) towards various elements outside of him. Based on the results of a preliminary study of 10 children aged 5-6 years, it was found that 5 children had normal development, 2 children doubted, and 3 children developed abnormally. While for family education conducted by parents, it was found that 7 parents supported (favorabel), and 3 parents were not supportive (unfavorable).Objectives: The study aimed to determine the influence of parents' attitudes in providing education at home toward the development of children aged 5-6 years in Bulusari Village, Gempol Sub-District, Pasuruan District.Methods: The research design was analytical design using purposive sampling with a sample of 45 parents and children in Bulusari Village, Gempol Sub-District, Pasuruan District. The measuring instrument used was a questionnaire for parents and KPSP for child development. This research is presented in the form of the Fisher's Exact Test.Results: The results showed that of 38 parents (84.45%) who supported having normal development children as many as 35 children (77.78%). Based on the results of the Fisher's Exact Test statistical test, it was found that the value of p <α, which is 0.001022 <0.05, which means that there is an influence from the provision of family education conducted by parents to the development of children aged 5-6 years.Conclusion: Based on the results of this study, it is expected that efforts from health workers to increase counseling to parents so that they have a role and have an obligation to help, assist children, teach children to actively learn, give love, develop creativity and socialization of children. Kata kunci : Parent’s attitude, development of 5-6 years, giving education in houses.